The effects of a selective Alpha-1 adrenergic blockade on the activity of adipose tissue lipoprotein lipase in female hamsters - Desfaits, Anne-Cécile; Lafond, Julie; Savard, Roland (Life sciences (1973), 1995)
Lipoprotein lipase, is an enzyme responsible for the hydrolysis of triacylglycerols at the surface of endothelial cells. Its regulation is not completely elucidated and seems, among other things, under the influence of the sympathetic nervous system. The adrenergic regulation of lipoprotein lipase activity is complex and the α 1 adrenergic pathway appears involved in this regulation. In the present study, adipose tissues of female hamsters are investigated following a single injection of doxazosin and phenylephrine and are compared to controls for the activity of lipoprotein lipase. After an acute treatment with a selective α 1 antagonist (doxazosin), lipoprotein lipase activity was decreased in the parametrial white adipose tissue and increased in brown adipose tissue (p <- 0.05). Moreover, a treatment with phenylephrine,' an α 1 adrenergic agonist, increased the activity of lipoprotein lipase, in the parametrial fat pad only. On the other hand, the activity of lipoprotein lipase in heart and in skeletal muscle was not modified by an α 1, stimulation or blockade. In this study, calcium and norepinephrine did not appear involved in the regulation of lipoprotein lipase activity. On the contrary, the increase of plasma glycerol after an acute treatment with doxazosin suggests that the lipolytic activity of white adipose tissue could be involved in the decrease of lipoprotein lipase activity in the parametrial white adipose tissue.